Hubungan Verbal Abuse Orang Tua Dengan Perkembangan Kognitif Pada Remaja Di SMP Negeri 2 Langowan Kabupaten Minahasa - Mangundap, Gabriel Meyti; Manoppo, Jeanette I.Ch; Kundre, Rina M. (Program Studi Ilmu Keperawatan Fakultas Kedokteran Universitas Sam Ratulangi, 2023)
Background: Verbal abuse is an act that hurts a child psychologically in verbal form that has adverse emotional consequences. Verbal abuse has a physical and psychological impact on adolescents and can interfere with growth and development, including cognitive development. Objective: this study is to determine the relationship between verbal abuse of parents and cognitive development in adolescents at SMP Negeri 2 Langowan. Method: this research uses a type of quantitative research with a correlation descriptive study that aims to analyze the relationship between two variables. With a cross-sectional study design and using verbal abuse and cognitive development questionnaires. The sample number was 59 people using nonprobability sampling techniques. Discussion: based on the results of research that there is verbal abuse of parents and have appropriate cognitive development can be caused by limited knowledge of parents in educating children so that it will have a negative impact while there is no parental verbal abuse and have a decline in cognitive development due to low memory causing poor learning ability and other factors because parents are busy with work so that lack supervision and direction from parents. Conclusion: this study is that there is a relationship between parental verbal abuse and cognitive development in adolescents at SMP Negeri 2 Langowan.